Elucidation of AIP related pituitary tumorigenesis - Ahlsten, Manuel (Helsingfors universitet, 2011)
Germline mutations in the aryl hydrocarbon receptor interacting protein (AIP) gene were recently shown to predispose to pituitary adenomas, which are neoplasms of the anterior pituitary gland. AIP mutations were first discovered in a cluster of familial pituitary adenomas in Northern Finland and afterwards in several populations worldwide. AIP associated pituitary adenomas are predominantly growth hormone secreting, thus several patients present with acromegaly or gigantism. The aim of this study was to elucidate AIP related pituitary tumorigenesis. AIP is suggested to be involved in several cellular pathways such as the xenobiotic response. In the cytosol, AIP interacts directly with aryl hydrocarbon receptor (AHR). After interaction with xenobiotic compounds AHR translocates to the nucleus and binds aryl hydrocarbon receptor nuclear translocator (ARNT). The AHR/ARNT heterodimer regulates the expression of several xenobiotic metabolizing enzymes. The AHR pathway is linked to e.g. the hypoxia response and estrogen signaling through ARNT and possibly through ARNT2, an ARNT homolog. A previously generated heterozygous Aip (Aip+/-) mouse model was used to study the role of these pathways in AIP-mediated tumorigenesis. Immunohistochemical studies revealed that expression of either ARNT or ARNT2 protein was lost in the mouse tumors. Aip+/- mice were also crossed and pregnant mice dissected to acquire Aip knockout (Aip-/-) and Aip wildtype (Aip+/+) embryos. Mouse embryonic fibroblast cell lines were prepared from these embryos and protein extracts were used for western blot analysis. This analysis revealed that expression of ARNT and ARNT2 was uniform between Aip-/- and Aip+/+ cell lines, which suggests that aberrant ARNT/ARNT2 expression is pituitary specific. In addition, Ki-67 analysis indicated that Aip deficient tumors have higher proliferation rates as compared with Aip proficient tumors. These results suggest that mechanisms of AIP related pituitary tumorigenesis involve aberrant ARNT/ARNT2 function, possibly ...